Characteristics, treatment patterns, and biomarker testing of patients with advanced RET fusion-positive non-small cell lung cancer in a real-world multi-country observational study: a brief report - Kiiskinen, Urpo; Segall, Grace; Bailey, Hollie; Forshaw, Cameron; Puri, Tarun (Frontiers in Oncology, 2025)
IntroductionApproximately 1−2% of non-small cell lung cancers (NSCLCs) are positive for rearranged during transfection (RET) gene fusions. The aim of this real-world multi-national study was to describe clinical characteristics, biomarker testing, and treatment patterns of patients with RET fusion-positive NSCLC.MethodsThis observational study was conducted in 2020 in nine countries using electronic patient record forms, following Adelphi Disease Specific Programme (DSP™) methodology. Patients with advanced NSCLC (aNSCLC) were included in the overall cohort. A smaller RET fusion-positive cohort comprised patients from the overall aNSCLC cohort who had RET fusion-positive disease and no other co-alterations, plus an oversample of patients with RET fusion-positive disease and no other co-alterations.ResultsPatient characteristics were generally similar between the overall aNSCLC cohort (n=2947) and the RET fusion-positive cohort (n=576), aside from higher proportions of White/Caucasian patients, never smokers, and adenocarcinoma among the RET fusion-positive cohort. For the overall aNSCLC cohort, 899 (31%) were tested for RET fusions; 84% of RET test results were available prior to initiation of aNSCLC treatment. Comparisons between the two cohorts showed similar proportions of patients treated with chemotherapy (± immunotherapy), but less use of immunotherapy only or targeted therapy in the RET fusion-positive cohort.ConclusionsResults of this real-world study provide insights into clinical characteristics, biomarker testing, and treatment patterns of patients with RET fusion-positive aNSCLC and highlight the need for awareness and education to increase RET testing with the intent to treat with selective RET inhibitors when appropriate to optimize outcomes for patients.